Ricerche antiquarie e linguistiche sui menonimi del calendario cappadoce (Atti del Sodalizio Glottologico Milanese, 2025)
This paper deals with the ancient month-names of the so-called “Cappadocian Calendar,” which was transmitted by several Byzantine manuscripts: the most relevant are the Laurentianus, Plut. 28.26, the Leidensis BPG 78, and the Vaticanus gr. 1291, but many other codices are known and were described by Western scholars during the last five centuries. The first pieces of information about the Cappadocian Calendar can be found in 16th-century treatises on astronomy and chronological calculations written in Latin. The state-of-the-art of the philological issues concerning the manuscript tradition, the secondary sources, and the former linguistic interpretations of the month-names are thoroughly presented in the first part of the work. In the second part, the etymologies of the philologically ascertained forms are offered. The linguistic results of the research validate the thesis that the “Cappadocian Calendar” dates back to the 4th century BC and contains Proto-Middle-Persian names, which confirm the Mazdaean origins of the Calendar. These terms mostly correspond to Young Avestan and New Persian month-names attested both in Iranian and Western texts.
Keywords: Cappadocia; Calendar; Month-Names; Old Persian; Iranian Philology